The internationalization of US writing programs - Rose, Shirley K., editor; Weiser, Irwin, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
Multiple theoretical approaches to the work of writing programs and WPAs play in defining goals, curriculum, placement, assessment, faculty and teacher development for international student populations.--Provided by publisher.
The internationalization of U.S. writing programs
The internationalization of United States writing programs
Internationalized writing programs in the 21st century United States: implications and opportunities / Irwin Weiser and Shirley K. Rose -- Writing program administrators in an internationalizing future: what's to know? / Christiane Donahue -- Writing programs and a new ethos for "globalization" / Margaret K. Willard-Traub -- Administrative structures and support for international L2 writers: a heuristic for WPAS / Christine M. Tardy and Susan Miller-Cochran -- Confronting "superdiversity" in U.S. writing programs / Jonathan Benda, Michael Dedek, Chris Gallagher, Kristi Girdharry, Neal Lerner, and Matt Noonan -- Contending with "difference": points of leverage for intellectual administration of the multilingual FYC course / Tarez Samra Graban -- It's not a course, it's a culture: supporting international students' writing at a small liberal arts college / Stacey Sheriff and Paula Harrington -- Expanding the role of the writing center at the "global" university / Yu-Kyung Kang -- "I am no longer sure this serves our students well": redesigning FYW to prepare students for transnational literacy realities / David Swiencicki Martins and Stan van Horn -- "Holding the language in my hand": a multilingual lens on curricular design / Gail Shuck and Daniel Wilber -- Intercultural communication and teamwork: revising business writing for global networks / Heidi A. McKee -- Building the infrastructure of L2 writing support: the case of Arizona State University / Katherine Daily O'Meara and Paul Kei Matsuda -- Developing faculty for the multilingual writing classroom / Jennifer E. Haan -- Internationalization from the bottom up: writing faculty's response to the presence of multilingual writers / Carolina Pelaez-Morales -- Infusing multilingual writers: a heuristic for moving forward / Libby Miles.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- United States; English language -- Rhetoric -- Study and teaching (Higher) -- Foreign speakers; Students, Foreign -- Education (Higher) -- United States; Multilingual persons -- Education (Higher) -- United States